Transitional Justice in Colombia The Special Jurisdiction for Peace - Ambos, Kai; Peters, Stefan (Studien zu Lateinamerika, 2022)
The Colombian Special Jurisdiction for Peace (Jurisdicción Especial para la Paz, JEP) is the judicial centrepiece of the country's national Transitional Justice system. At the same time, the JEP is also at the centre of public controversies surrounding the Colombian peace process and is facing a series of legal and political challenges in its daily work. In this sense, the JEP generates a continuous need for consultation, discussion and research. The articles in this volume aim to contribute to a better understanding of the JEP and to identify further necessary research avenues on this topic. At the same time, we hope to contribute to the still limited research on the Colombian peace process and the JEP in the English language.